Some South African red seaweed polysaccharides - Clingman, Abraham Lionel (Department of Chemistry, 2016)
Algae have been classified by botanists into four large groups: the Chlorophyceae or green algae, the Phaeophyceae or brown algae, the Rhodophyceae or red algae, and the Cyanophyceae or blue-green algae. The polysaccharides which are extracted from marine algae may be differentiated into reserve polysaccharides, analogous to starch in land plants, and into structural polyrsaccharides, analogous to cellulose in land plants. Laminarin from brown seaweeds and Floridean starch from certain red algae are reserve polysaccharides while algihates (from brown seaweeds) and carrageenin and agar (from red seaweeds) are structural polyrsaccharides. The most common encountered algal polycysaccharides, besides alginic acid, are agar and carrageenin. These are salts of sulphate esters of polysaccharides which contain D-galactose. Agar and carrageenin mucilages are obtained by aqueous extraction from certain red seaweeds of the class Florideae. Agar is extensively used in the meat canning and confectionery trades where it has to a very large extent replaced gelatin. Nearly all the South African production of agar is used in this way. Carrageenin is used in brewing as a clarifying agent, as a stabilising agent in cocoa and in a large number of pharmaceutical products.